Online Teaching Practicum: Elucidating Student Teachers’ Perception and Improvement in ELT - Miftahul Mahrus; Novinda Rosayanti; Gusti Puspita Nirwana (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2023)
Conducting teaching practicum during the Covid-19 Pandemic has become big challenges for the student teachers because it changes many aspects of human life including the educational aspect. This requires student teachers to have more preparation for teaching because they have to make the materials, strategies, and media are appropriate for the current situation in English Language Teaching (ELT). Therefore, this study aims to investigate the student teachers’ perception also improvement perceived toward the implementation of their teaching practicum at the graduate level at one of the state universities in East Java, Indonesia. Survey with a qualitative approach was used as the research design. The participants were 38 student teachers who have taken teaching practicum course in the third semester. A close-ended questionnaire and Interviews were used to see the student teachers’ perception and improvement of the implementation of their teaching practicum. In analyzing the data from the questionnaire, the researchers classified the scale (1-2) indicates negative and (3-4) indicates positive perception and improvement perceived towards the implementation of teaching practicum. Meanwhile, the data from the interviews were analyzed thematically. The results of data analysis show that the student teachers have a positive perception. Also, the student teachers perceived improvement of the implementation of teaching practicum. This study will be used as the references for the practitioner, curriculum developer, and the teacher in higher education to consider the student teachers’ perception towards the implementation of the teaching practicum.